Un análisis pragmático del rumor a propósito de la columna: “No nos consta” de Tola y Maruja (2002)
In this paper, the purpose is to analyze Tola and Maruja’s discourse, as it is being published in Sunday newspaper “El Espectador”. Even though, we know these characters are discursive make ups of two men from Medellin, Carlos Mario Gallego and Sergio Valencia, we are interested precisely in focusing on what they represent In our context “Tola y Maruja” when they show un in scene and with respect to which these last two are marginal.Tola y Maruja are two lower class women who represent the majority, namely the poor people. They have no Inherence whatsoever in terms of power and social control. However, it is precisely this condition of marginality that lends then generate policy of civic resistance through one of the most effective every day practices: Rumor. This, together with a strong force of sarcastic humor, becomes a very efficient mode of social criticism.